Information and Technological Skills of UNAM's Library Students - Castillo Rojas, Selene Violeta (2022)
Information and communications technology (ICT) have become an important key to improve the educative process and documentary resources in digital format are the axis of this process, so students must acquire and / or develop a series technological and information skills that allow you to obtain quality information, with academic validity and relevance for your academic activities. This work refers to a diagnosis of the skills that students of Library Science and Information Studies of the National Autonomous University of Mexico possess,which allow establishing strategies to optimize the development of these skills.